Severe Leptospirosis (Weil’s Disease) Complicated by Septic Shock: A Case Report - Andrean, Melvin; Sasongko, Calvin; Nabil Mubtadi Falah (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Weil’s disease is the severe manifestation of leptospirosis, characterized by multiorgan dysfunction and high mortality risk without timely diagnosis and treatment. Early clinical suspicion and prompt intervention are critical for favorable outcomes. Case Illustration: a 51-year-old male with fever, left leg myalgia, jaundice, hypotension, and tachycardia consistent with septic shock. Laboratory evaluation revealed leukocytosis, acute liver injury, and severe acute kidney injury. Additionally, chest imaging revealed bilateral pulmonary infiltrates. Initial management included fluid resuscitation, vasopressors, and broad-spectrum antibiotics. Leptospira IgM serology confirmed the presence of leptospirosis on day 2. Despite severe acute kidney injury, renal function improved without dialysis, and vasopressors were discontinued by day 3. The patient was discharged on day 11, having made a full recovery. Discussion: Severe leptospirosis can present with nonspecific symptoms and progress to septic shock and multiorgan dysfunction. In this case, the diagnosis was supported by IgM-ELISA and a history of exposure to floodwater. Early treatment with broad-spectrum antibiotics and supportive care led to a full recovery. Conclusion: This case highlights the uncommon presentation of septic shock as the dominant feature of Weil’s disease, together with rapid renal recovery without dialysis, underscoring the reversibility of multiorgan dysfunction when promptly managed.